Innovation, sustainable HRM and customer satisfaction. (January 2019) - Wikhamn, Wajda
Highlights: Sustainable HR practices are important for customer satisfaction and for producing innovations in hotels. Less innovative hotels with a strong sustainable HR profile have equally satisfied customers compared to innovative hotels. Innovation and sustainable HR practices substitute, rather complement, each other to achieve superior customer satisfaction. Abstract: The purpose of this paper is to explore how sustainable human resource management (HRM) practices impact the innovation-customer satisfaction relationship in Swedish hotels. Responding hotels were profiled into four groups based on their involvement in two sustainable HR practices. The findings indicate the relationship between innovation and customer satisfaction is dependent on sustainable HR practices in the organization. Although innovation and sustainable HR practices impact customer satisfaction positively, their interaction suggests that the one can substitute the other to achieve superior customer satisfaction. The study concludes that sustainable HR practices enhance a hotel's capability to innovate and to have satisfied customers. The relationship between sustainable HR practices and innovation is discussed.